Assurance of the Effectiveness of Corporate Insolvency Proceedings - Tamošiūnienė, Egidija; Višinskis, Vigintas; Kirkutis, Mykolas; Jokubauskas, Remigijus (Teisė, 2020)
This article examines some practical problems of the application of the Law on the Insolvency of Enterprises of the Republic of Lithuania related to the effectiveness of insolvency proceedings. Though the new insolvency law seeks to ensure effective insolvency process, the analysis of certain provisions reveals certain problems of this act, which could significantly impact the effectiveness of this process.
Keywords: insolvency; insolvency proceedings; effectiveness of insolvency proceedings